Enlightened Monks: The German Benedictines, 1740–1803 - Monson, Paul G. (A journal of church and state, 2011)
When positing the role of Benedictine monasticism in church history, the scholar often looks to medieval exemplars such as Cluny. The thought of monks in the Age of Reason seems counterintuitive, and the concept of “enlightened monks” suggests an oxymoron. However, it is precisely the image of the erudite, reform-oriented monk that Ulrich Lehner recovers in his curious history of eighteenth-century Benedictine thought and culture. By his own admission, Lehner follows in the footsteps of Derek Beale's Prosperity and Plunder (2003), advancing a revisionist historiography of early modern monasticism. Enlightened Monks, however, focuses on the Reich and reveals the complexity of German Catholic engagement with the new ideas of the age.